SIMULASI HIDRAULIK ELEVASI MUKA AIR SALURAN RAWASARI MENGGUNAKAN HEC-RAS - Amiruddin, Aswar; Widiyanti, Aneza Ferdani (Civil Engineering Scientific Journal, 2025)
The Rawasari Channel is one of the channels in the West Tarakan Subdistrict that supplies water for the availability of water in the city of Tarakan. However, the Rawasari Channel sometimes experiences overflow during high rainfall intensity. The purpose of this research is to determine the water level in the Rawasari Channel through hydraulic simulation using HEC-RAS software. The repeated flood discharge periods used as parameters for this research are 50 years and 100 years, calculated using the Rational method. The flood discharge analysis results using the Rational method for a 50-year recurrence period are 21,098 m3/s, and for a 100-year recurrence period, it is 21,399 m3/s. Based on the HEC-RAS simulation, there is no significant difference in water surface elevations due to the 50 and 100-year floods. From the HEC-RAS simulation, it is also known that due to the flood discharge of 50 and 100 years, overflow occurs in the Rawasari Channel at stations STA 350, 325, 300, 150, and 125. The water surface elevation due to the 50-year flood at STA 350 is 20.38 m, and for STA 300, the water surface elevation for the 50-year flood is 20.29 m. The elevation of the land surface around STA 350 and STA 300 ranges from 19.99 m to 20.19 m, so the height of the inundation due to the overflow of the Rawasari Channel is known to be between 11 cm and 30 cm.